-(y+13)/49=-40

Simple and best practice solution for -(y+13)/49=-40 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(y+13)/49=-40 equation:



-(y+13)/49=-40
We move all terms to the left:
-(y+13)/49-(-40)=0
We add all the numbers together, and all the variables
-(y+13)/49+40=0
We multiply all the terms by the denominator
-(y+13)+40*49=0
We add all the numbers together, and all the variables
-(y+13)+1960=0
We get rid of parentheses
-y-13+1960=0
We add all the numbers together, and all the variables
-1y+1947=0
We move all terms containing y to the left, all other terms to the right
-y=-1947
y=-1947/-1
y=+1947

See similar equations:

| -4(6x+9)=-2(12x+18) | | 398-a)=12 | | 275+d=1091/12 | | G(x)=x²+6x | | 15-1/2n=7 | | 10x^2+160=0 | | 2=8–2m | | 5=y/y-3=14/10 | | 1/5(x-20=44 | | 12=2u-14 | | 2–-2n=-4 | | b+2.9=8.7 | | 6,3x+9=7,2x-4,5x | | 5u+9=94 | | 10=7+-3q | | -5m+2.5=16.5 | | x/8+12=-12 | | (n-3)/6=(2n)/14 | | -s–9=2s+9 | | 2u-9=25 | | c/25=3.5 | | 9(p-2)=90 | | 16x-4=4=(2x-3) | | -8u+6(u+7)=32 | | 46.50=2/3x+2.50 | | 12=6x-7x=3x-2x | | 9y+19=-8 | | 1/3×1/7(184-x)=8 | | w/10=-5.2 | | 4x-2(3+3x)=-86 | | 71=4x+11 | | 6+x/x=x/2+3 |

Equations solver categories